The R3-N3 and R5-N5 Palaeomagnetic Transition Zones in SW-Iceland Revisited. (Dataset) ... - Kristjansson, Leo; Sigurgeirsson, Magnus (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: The R3-N3 and R5-N5 Palaeomagnetic Transition Zones in SW-Iceland Revisited. ...